MY SAY: Obama the gamechanger - Abd Razak, Dzulkifli (2009)
US President Barack Hussein Obama is now the Nobel Peace Prize Winner for 2009. It's almost like a dream. Many have hailed the decision, and the audacity of hope put on him. But not everyone agrees. A stunned fellow laureate and former Polish president Lech Walesa quipped: "So soon? Too early." The Financial Times called it the "Urgency of Now". Still, others have nightmares, especially from the "enemy" camp. Obama's predecessor George W Bush, after all, had tried very hard to bring peace, but only managed to get a shoe thrown at him! Obama, on the other hand, hardly tried and voila! got the real thing, barely 240 days into his presidency. Others have suggested that the award is meant to shame the former president.